EURADOS intercomparison on emergency radiobioassay. Issue 4 (27th December 2014) - Li, Chunsheng; Battisti, Paolo; Berard, Philippe; Cazoulat, Alain; Cuellar, Antonio; Cruz-Suarez, Rodolfo; Dai, Xiongxin; Giardina, Isabella; Hammond, Derek; Hernandez, Carolina; Kiser, Stephen; Ko, Raymond; et al.
Abstract: Nine laboratories participated in an intercomparison exercise organised by the European Radiation Dosimetry Group (EURADOS) for emergency radiobioassay involving four high-risk radionuclides ( 239 Pu, 241 Am, 90 Sr and 226 Ra). Diverse methods of analysis were used by the participating laboratories for the in vitro determination of each of the four radionuclides in urine samples. Almost all the methods used are sensitive enough to meet the requirements for emergency radiobioassay derived for this project in reference to the Clinical Decision Guide introduced by the NCRP. Results from most of the methods meet the requirements of ISO 28218 on accuracy in terms of relative bias and relative precision. However, some technical gaps have been identified. For example, some laboratories do not have the ability to assay samples containing 226 Ra, and sample turnaround time would be expected to be much shorter than that reported by many laboratories, as timely results for internal contamination and early decisions on medical intervention are highly desired. Participating laboratories are expected to learn from each other on the methods used to improve the interoperability among these laboratories.